2020
DOI: 10.1042/bsr20194405
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate antigen-125, calcium, and hemoglobin as predictive clinical indicator for ocular metastasis in male liver cancer patients

Abstract: Background Primary liver cancer (PLC) is a common type of cancer among men worldwide. Little is known regarding the relationship of liver cancer with ocular metastasis (OM). Drinking has been also reported to be related not only to the occurrence of liver cancer but also to the causes of some ocular lesions. Purpose A diagnostic standard for the levels of serum biomarkers associated with OM derived from liver cancer in men is urgently needed. Material and methods We examined the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…β-globin is selectively increased in cancer cells, mediating a cytoprotective effect during blood-borne metastasis [40]. The normal adult hemoglobin is a predictive clinical indicator for liver cancer combining with combined with CA-125 [35]. In this study, we observed that the expression of hemoglobin, especially HbF, dramatically alters during tumorigenesis of HCC.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…β-globin is selectively increased in cancer cells, mediating a cytoprotective effect during blood-borne metastasis [40]. The normal adult hemoglobin is a predictive clinical indicator for liver cancer combining with combined with CA-125 [35]. In this study, we observed that the expression of hemoglobin, especially HbF, dramatically alters during tumorigenesis of HCC.…”
Section: Discussionmentioning
confidence: 66%
“…As a non-invasive screening of tumors, blood testing, has been paid more and more attention. In addition to circulating tumor cells in peripheral blood, some factors released by tumor cells were found in plasma, and a large number of tumor biomarkers were characterized including CA125 and AFP, of which CA125 is also a sensitive factor in liver cirrhosis [34,35]. The transcriptional information carried by platelets in peripheral blood can be utilized to judge the occurrence and type of tumors [13].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing attention has been paid to blood testing as a non-invasive screening for tumors. In addition to circulating tumor cells in peripheral blood, some factors released by tumor cells are found in plasma, and a large number of tumor biomarkers is characterized, including CA125 and AFP, of which CA125 is also a sensitive factor in LC [ 37 , 38 ]. Transcriptional information carried by platelets in peripheral blood can be utilized to estimate the onset and type of tumors [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a cut-off of 2.5 mmol/L of calcium could identify bone metastases in bladder cancer patients with a sensitivity of 32% and a specificity of 94%, with high calcium levels providing an increased risk of metastasis (OR = 13.049, CI: 3.836–44.384, p -value < 0.001) [ 182 ]. A cut-off of 2.7 could identify HCC patients at risk of ocular metastasis with a sensitivity of 19% and a specificity of 97%, with high calcium levels providing an OR of 1.062 (CI: 1.028–1.096) for the risk of metastasis [ 183 ].…”
Section: Calciummentioning
confidence: 99%